Main gateway to Santa Clara University - Johnson, Charles Elllis (photographer):::Creator::::::::::::
Street view of the main entrance to Santa Clara University. On the far left the smoke stacks of a industrial facilty can be seen down the road from the university. On the campus, a variety of the buildings and grounds can be seen, including what appears to be a chapel for the university.